N. C. Craig Sharp. (28th April 2018) - Jarrett, Oswald; Murray, Max; Boyd, Jack; Wright, Norman
Abstract : A vet whose journey took him from veterinary physiology, through pathology to sports science, a field in which he was world‐renowned.